2003
DOI: 10.1259/dmfr/25091144
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of increased capsular width as a predictor of temporomandibular joint effusion

Abstract: Analysis of ROC curve appears to reveal that the critical area is around the 2 mm value for TMJ capsular width. These findings need to be refined by further studies assessing the smallest detectable difference in capsular width, with attention to reliability of interobserver observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 20 publications
7
47
0
1
Order By: Relevance
“…23 The majority of symptomatic participants (75%) had mean capsular widths spanning 0.19 cm or above. This is above the level found by Manfredini et al 18 to be a good critical level to assess effusion. However, histological and biomarker studies would be needed to fully assess the accuracy of using ultrasound to diagnose inflammation.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…23 The majority of symptomatic participants (75%) had mean capsular widths spanning 0.19 cm or above. This is above the level found by Manfredini et al 18 to be a good critical level to assess effusion. However, histological and biomarker studies would be needed to fully assess the accuracy of using ultrasound to diagnose inflammation.…”
Section: Discussionmentioning
confidence: 45%
“…Ultrasound diagnosis of effusion has been favourably compared to the gold standard MRI scan, especially when the capsular width is above 1.950 mm. 18 It should be noted that it has been reported that the TMJ is one of the hardest joints in the body to scan, 19 and a standard protocol for diagnosing TMJ derangement has not been agreed upon by ultrasonographers. 20 No prior studies on correlation between TMJ effusion and patient disability have been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…20 To discriminate between internal derangement joints with and without effusion, a cut-off value of 1.65 mm was found. 21 Manfredini et al 23 proposed a capsular width cut-off value of 2 mm, assessed at the condylar level in a longitudinal scan, as an indirect marker of TMJ effusion in adults with temporomandibular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation between the articular disc and capsule was undertaken in accordance with the criteria of Emshoff et al, 13 who reported that the two hyperechoic lines in TMJ sonograms are related to the condylar head and articular eminence cortices and the hypoechoic area between them is produced by the articular disc. In contrast, Manferedini et al 14 suggested that these hyperechoic lines are the articular capsule and the lateral condylar wall. The study described here was double-blind.…”
Section: Methodsmentioning
confidence: 94%
“…5,6 Some authors have recently reported the application of high-resolution ultrasonography (HR-US) to the examination of the TMJ and other joints of the body. [7][8][9][10][11][12][13][14][15] Ultrasonography is a noninvasive, low-cost imaging technique that is readily accessible and easy to perform. The use of harmless ultrasound waves instead of ionizing radiation also means that ultrasonography is more accepted by patients.…”
Section: Introductionmentioning
confidence: 99%